Hubungan Hipertensi Dengan Penyakit Arteri Perifer Di Posyandu Lansia Kelurahan Pucangan Tinjauan Terhadap Nilai Ankle Brachial Index - Fatayati, Imma; , Isnaini Herawati, S. Fis, M.Sc (2017)
Background: Hypertension is a conditional of blood pressure above normal circumstances, if not controlled in the long term can lead the stroke, heart attack, heart failure, and the main cause of chronical renal failure. Hypertension is a risk factor of cardiovascular disease which one of them is peripheral arterial disease. People with cardiovascular disease have a high prevalance of hypertension by 80%. For diagnosis using ankle brachial index assessment, as lower as the value of ankle brachial index as higher as the number of deaths with cardiovascular disease and including peripheral arterial disease. Purpose: To determine the relationship of hypertension with peripheral arterial disease in term of ankle brachial index. Method: This research is an observational research with cross sectional method. Technical sampling using quota sampling of 224 respondens. Primary data taken from the assessment status of hypertension and peripheral arterial disease using sphygmomanometer and stethoscope.the data status of hypertension strengthened with secondary data from medical record of responden. The data status of peripheral arterial disease is measure by ankle brachial index carried out after the break 5-30 minutes. Statistical testing using chi square test. Result: From 224 people, 38 (17,05%) people have status of hypertension with the value of ankle index occlusion, and 36 (16,15%) people have status of hypertension with the value of ankle brachial index calcification. After the chi square test showed the value p<0,002 which shows the relationship between variable of hypertension and ankle paripheral arterial disease. It mean individuals with hypertension has a risk 2,004 times odds peripheral arterial disease. Conclution: there is a relationship betwen hypertension and peripheral arterial disease which reviewed by a value of ankle brachial index.